Impact of Social Cognition on Alcohol Dependence Treatment Outcome: Poorer Facial Emotion Recognition Predicts Relapse/Dropout. (10th November 2017) - Rupp, Claudia I.; Derntl, Birgit; Osthaus, Friederike; Kemmler, Georg; Fleischhacker, W. Wolfgang
Abstract : Background: Despite growing evidence for neurobehavioral deficits in social cognition in alcohol use disorder (AUD), the clinical relevance remains unclear, and little is known about its impact on treatment outcome. This study prospectively investigated the impact of neurocognitive social abilities at treatment onset on treatment completion. Methods: Fifty‐nine alcohol‐dependent patients were assessed with measures of social cognition including 3 core components of empathy via paradigms measuring: (i) emotion recognition (the ability to recognize emotions via facial expression), (ii) emotional perspective taking, and (iii) affective responsiveness at the beginning of inpatient treatment for alcohol dependence. Subjective measures were also obtained, including estimates of task performance and a self‐report measure of empathic abilities (Interpersonal Reactivity Index). According to treatment outcomes, patients were divided into a patient group with a regular treatment course (e.g., with planned discharge and without relapse during treatment) or an irregular treatment course (e.g., relapse and/or premature and unplanned termination of treatment, "dropout"). Results: Compared with patients completing treatment in a regular fashion, patients with relapse and/or dropout of treatment had significantly poorer facial emotion recognition ability at treatment onset. Additional logistic regression analyses confirmed these results and identified poor emotion recognition performance as a significant predictor for relapse/dropout. Self‐report (subjective) measures did not correspond with neurobehavioral social cognition measures, respectively objective task performance. Analyses of individual subtypes of facial emotions revealed poorer recognition particularly of disgust, anger, and no (neutral faces) emotion in patients with relapse/dropout. Conclusions: Social cognition in AUD is clinically relevant. Less successful treatment outcome was associated with poorer facial emotion recognition ability at the beginning of treatment. Impaired facial emotion recognition represents a neurocognitive risk factor that should be taken into account in alcohol dependence treatment. Treatments targeting the improvement of these social cognition deficits in AUD may offer a promising future approach. Abstract : This study prospectively investigated the impact of neurocognitive social cognition abilities at the beginning of treatment on treatment outcome with regard to relapse and/or drop‐out in alcohol‐dependent patients. Neurobehavioral social cognition measures were complemented with self‐report measures. We found that poorer facial emotion recognition in alcohol‐dependent patients at treatment entry negatively impact upon treatment success (relapse/dropout), and thus represents an early identifiable neurocognitive risk factor that should be taken into account in alcohol dependence treatment.